Ferritin-armed extracellular vesicles with enhanced BBB penetration and tumor-targeting ability for synergistic therapy against glioblastoma - Guihong Lu; Peiling Zhuang; Feng Li; Fan Zhang; Xiaoyan Li; Weixiu Wang; Hui Tan (Journal of Nanobiotechnology)
Abstract Glioblastoma multiforme (GBM) is an aggressive brain cancer with a high mortality rate and limited treatment options. Metabolism-based synergistic therapy holds promise for GBM treatment, however, its efficacy is significantly impeded by poor blood-brain barrier (BBB) penetration, inadequate targeting of GBM cells, and systemic drug-related side effects. To address these challenges, we herein developed a dual-targeting nanoplatform, EVs@siMCT4-HFn@AuMn, by arming siMCT4-loaded M1-type microglia-derived extracellular vesicles (EVs) with ultrasmall nano-Au/MnO2-loaded H-ferritin (HFn). This nanoplatform enhances tumor accumulation through cooperative BBB penetration and the GBM-targeting properties of EVs and HFn. Within the GBM microenvironment, siMCT4 silences MCT4 expression, inhibitits lactate (LA) efflux, increases the intracellular LA levels to induce glioma cell apoptosis via LA metabolic therapy, and reduces extracellular LA to achieve M2-to-M1 polarization of tumor-associated macrophages for immunomodulation of the tumor microenvironment. Concurrently, the delivered ultrasmall nano-Au consumes glucose for starvation therapy and facilitates H2O2 production, which is utilized by the co-delivered ultrasmall nano-MnO2 to generate cytotoxic hydroxyl radicals (•OH), further enhancing tumor cell eradication. This synergistic approach effectively suppresses tumor growth in a glioma xenograft model with negligible side effects, highlighting the potential of EVs@siMCT4-HFn@AuMn as a flexible and powerful platform for metabolism-based multimodal GBM therapies. Graphical abstract